2014
DOI: 10.1038/sj.bdj.2014.523
|View full text |Cite
|
Sign up to set email alerts
|

Dental students' uptake of mobile technologies

Abstract: Depending on the year in the course, laptops and smartphones are the most popular choice of device and desktop computers are the least popular. Applications on smartphones are very popular and instant messaging is an upcoming form of communication for students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
46
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 20 publications
(29 reference statements)
12
46
0
3
Order By: Relevance
“…This figure is similar to that reported for dental students in New Zealand (98%) (8) but higher than that reported by dental students in England (55%) (9). Technology should enhance the educational process, if used properly.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This figure is similar to that reported for dental students in New Zealand (98%) (8) but higher than that reported by dental students in England (55%) (9). Technology should enhance the educational process, if used properly.…”
Section: Discussionsupporting
confidence: 78%
“…Technology should enhance the educational process, if used properly. In developed countries, for example, researchers evaluated the extent to which such technologies are utilized, and/or how they can enhance learning (8)(9)(10)(11)(12)(13). In addition, it has been suggested that SN can be a valuable learning source for dental practitioners and their patients (6).…”
Section: Discussionmentioning
confidence: 99%
“…This opinion is borne out by a significant body of evidence relating to the stress experienced by dental students. 67 However, in a recent study 68 only 11% of undergraduates stated that they would find a stress management app for a smart phone helpful. The dentists felt that stress management training would need to be distinguished from communication skills training, which some felt was aimed at 'communicat[ing] to avoid legal problems.'…”
Section: Theme 10: Stress Management Training Needs (Code 22)mentioning
confidence: 97%
“…6 In that study, the authors compared the results of an assessment of two groups, one using traditional teaching and the other using the same method plus WhatsApp. 9 Some authors had suggested that WhatsApp should be used for teaching and learning in order to improve students' performance. Similar positive results were reported when WhatsApp was used for teaching and discussing cases of dental radiology.…”
Section: Does Time Matter? Whatsapp Vs Electronic Mail For Dental Edumentioning
confidence: 99%
“…Similar positive results were reported when WhatsApp was used for teaching and discussing cases of dental radiology. 9 Furthermore, some evidence suggests that students felt motivated when using WhatsApp as it favoured the learning experience making it more amenable. 9 Some authors had suggested that WhatsApp should be used for teaching and learning in order to improve students' performance.…”
Section: Does Time Matter? Whatsapp Vs Electronic Mail For Dental Edumentioning
confidence: 99%